Corporate governance effects on social responsibility disclosures - Dias, António (2017)
This study uses stakeholder theory to explore how corporate governance [CG] characteristics influence corporate social responsibility disclosure [CSRD] in the context of a global financial crisis [GFC]. Empirical data are drawn from Portugal, a country strongly affected by the GFC. Portuguese companies are characterized by high ownership concentration. The largest shareholder is often the CEO and Board Chair (a phenomenon known as CEO duality). We analyse the association between CSRD (measured by a 40-item disclosure index) and CG variables (board size, CEO duality, board independence, ownership concentration and presence of an audit committee or CSR committee) for 48 of the 51 listed companies in Portugal. The control variables are company size and industry type. We find that CSRD is affected positively by board size, CEO duality, company size and industry type. This accords with suggestions implicit in stakeholder theory that a larger board will represent a broader diversity of stakeholders and will promote better monitoring, more assertive stakeholder management, greater transparency, and increased levels of CSRD. Larger companies and companies close-to-consumers are associated with high levels of CSRD, ostensibly because they are more visible and subject to greater societal monitoring during a period of financial crisis. We reveal that in a country characterized by high ownership concentration, CEO duality has a positive effect on CSRD.